Impact of Testosterone Therapy on Major Cardiovascular Risk in Erectile Dysfunction Patients with Testosterone Deficiency - Poopuangpairoj T; Sirisopana K; Ketsuwan C; Kongchareonsombat W; Phengsalae Y; Matang W; Sangkum P (Research and Reports in Urology, 2024)
Tanawin Poopuangpairoj, Kun Sirisopana, Chinnakhet Ketsuwan, Wisoot Kongchareonsombat, Yada Phengsalae, Wijittra Matang, Premsant Sangkum Division of Urology, Department of Surgery, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Premsant Sangkum, Division of Urology, Department of Surgery, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand, Email premsanti@gmail.comObjective: The objective of this study was to evaluate major adverse cardiovascular events in erectile dysfunction (ED) patients who received testosterone replacement therapy (TRT) compared with those who did not.Materials and Methods: From January 2012 to October 2021, we collected the retrospective data of patients with ED at Ramathibodi Hospital. We divided the patients into two groups: those who received TRT (TRT group) and those with normal testosterone levels and therefore not requiring TRT (non-TRT group). The patients’ baseline clinicodemographic data were collected. Major adverse cardiovascular events, including cardiovascular death, ST- and non-ST-elevation myocardial infarction, hospitalization from congestive heart failure, transient ischemic attack, and ischemic stroke, were collected and analyzed within 2 years after treatment in all groups.Results: Of the 221 patients, 111 were in the TRT group and 110 were in the non-TRT group. In the non-TRT group, one event each of the following occurred: myocardial infarction, transient ischemic attack, and stroke. In the TRT group, no major cardiovascular event occurred during the 2-year follow-up period. However, no significant difference in major cardiovascular events was noted between the two groups (p = 0.314).Conclusion: TRT in ED patients with testosterone deficiency does not increase adverse cardiovascular events when compared with ED patients with normal testosterone level.Keywords: erectile dysfunction, testosterone deficiency, testosterone replacement therapy, major adverse cardiovascular events